Overcoming Inequalities in Schools and Learning Communities: Innovative Education for a New Century - Garcia-Carrion, Rocio; Rodrigues De Mello, Roseli; Ball, Arnetha F. (Frontiers Media SA, 2020)
Educational inequalities have strongly impacted disadvantaged and underserved populations such us indigenous, Roma, migrant children, students with disabilities, and those affected by poverty. A wide array of research has contributed to explaining the mechanisms and effects of inequalities in the achievement patterns, dropout rates, disengagement in the school experiences of children and youth traditionally excluded. Research also suggests the negative consequences for child development - including cognitive, language, and social-emotional functioning - of poverty and lack of quality education in the early years. Consequently, the current unequal access to optimal learning environments for every single child to succeed in education and to have a better life perpetuates the exclusion and neglects the right to education for those minorities. This Research Topic aims at moving beyond causes and shed light upon effective solutions by providing successful pathways for integration and inclusion of the learners most heavily affected. Scholars worldwide are looking for successful actions with children, youth, and communities of learners historically underserved to overcome educational and social exclusion. These transformative approaches go beyond the deficit thinking and are grounded in theories, empirical evidence, and multidisciplinary interventions oriented towards achieving social impact, which refers to the extent to which those actions have contributed to improve a societal challenge. The international network of "Schools as Learning Communities" is advancing knowledge on deepening and expanding the impact of what has been defined as Successful Educational Actions (SEAs); that is, those interventions that improve students' achievement and social cohesion and inclusion in many diverse contexts, regardless the socioeconomic, national, and cultural environment of schools. Drawing on the evidence generated by this network of researchers to address the global challenge of inequality by studying educational actions oriented towards achieving social impact and potentially transferrable to other contexts, this Research Topic aims at deepening on this approach. In short, our purpose is that the contributions included in this Research Topic contribute to reduce educational and social inequalities and especially benefit those populations most in need.